Pengrajin Kulit Kerang dalam Meningkatkan Kesejahtraan Keluarga di Desa Batu Merah Kecamatan Sirimau Kota Ambon - Dwi Dewi Fitriani; Lambertus J. Lokollo; J.L. Kundre (Peneliti.net, 2021)
Artwork is a process of creation from work and the presentation of ideas or ideas that humans have for satisfaction in terms of beauty. Regarding applied art, it is a creation of artistic value and the function of a craftsman. Various Indonesian cultural wisdoms are certainly synonymous with the well-known handicrafts, all over the plains of the archipelago have diversity, characteristics and different styles in each region. Crafts are jobs or activities related to handmade or hand-crafted activities. family welfare in the 70s and 80s had a good increase in family welfare, but nowadays it is not as uncertain as it used to be because the welfare of the family now depends on the many orders that order the seashell crafts, if many order a lot then the increase in family welfare from you are very good and improving, and for the 2020s there has been no increase in family welfare especially the corona which has made you not have any improvement. This is due to the lack of increased income which is at a sufficient level and even does. This research is descriptive quantitative in which the author tries to explain systematically about aspects that exist in the community in relation to shellfish craftsmen in Batumerah Village, Sirimau District, Ambon City. Thus, the research uses a case study approach to the benefits of shellfish techniques, the subjects in this study are 2 Respondents of Seashell Craft. The results of this study explain that the family welfare of the seashell craftsmen is sufficient for the family's needs.